Once-daily rivaroxaban for long-term stroke prevention in patients with atrial fibrillation. (20th April 2016) - Antoniou, Sotiris; Amara, Walid
Abstract: Oral anticoagulation is the long-term standard of care for preventing stroke in patients with atrial fibrillation (AF). However, anticoagulation is associated with an increased risk of bleeding, such that its use should be based on the absolute risks of stroke and bleeding, and the relative benefit–risk profile of the individual patient. Non-vitamin K antagonist oral anticoagulants, including rivaroxaban, are alternatives to vitamin K antagonists such as warfarin in this setting, and are supported in treatment guidelines as the optimal choice for patients with AF at moderate to high risk of stroke. Rivaroxaban can be given in fixed doses without routine coagulation monitoring, and phase III studies have demonstrated its safety profile and efficacy in patients with non-valvular AF, including the elderly and those with co-morbidities. Moreover, rivaroxaban is administered once daily, which has advantages for optimal patient adherence to medication over the long term. The established efficacy and safety profile of rivaroxaban, together with its convenient once-daily dosing schedule, may contribute to improved patient outcomes and lead to sustained benefits for patients with non-valvular AF at risk of stroke.